2011
DOI: 10.1111/j.1398-9995.2011.02693.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of efficacy of long‐term, low‐dose azithromycin in chronic rhinosinusitis: a randomized controlled trial

Abstract: At the investigated dose of AZM over 3 months, no significant benefit was found over placebo. Possible reasons could be disease severity in the investigated group, under-dosage of AZM and under-powering of the study. Therefore, more research is urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
171
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(184 citation statements)
references
References 37 publications
6
171
2
5
Order By: Relevance
“…However, a recent study including 60 patients with recalcitrant CRS (with and without nasal polyps) unresponsive to optimal medical or surgical treatment, reported no significant differences in symptom scores or objective measures after a 3-month course of azithromycin compared with placebo [95], highlighting the need for matching patient characteristics, drug-administered and outcome measures before comparing the results of different studies.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
“…However, a recent study including 60 patients with recalcitrant CRS (with and without nasal polyps) unresponsive to optimal medical or surgical treatment, reported no significant differences in symptom scores or objective measures after a 3-month course of azithromycin compared with placebo [95], highlighting the need for matching patient characteristics, drug-administered and outcome measures before comparing the results of different studies.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
“…Videler et al 753 examined CRSsNP patients and CRSwNP patients with low-grade polyps using a similar combination of patient-reported outcome and objective measures and found that azithromycin 500 mg/week after an initial loading dose showed no benefit over placebo. Notably, CRSwNP patients comprised 52% of the 60 subjects.…”
Section: Viie4 Crssnp Management: Antibioticsmentioning
confidence: 99%
“…Gastrointestinal disorders including mild diarrhea, vague abdominal discomfort, or nausea and vomiting were most common, reported in less than 5% of all patients. 753,754,761 In non-sinus studies, macrolides have been implicated in causing ototoxicity 764 and liver dysfunction. 765 Concerns about overuse resulting in host antibiotic resistance have been raised.…”
Section: Viie4 Crssnp Management: Antibioticsmentioning
confidence: 99%
“…There was a favorable response in the roxithromycin treatment group in terms of patient response score (Ϫ0.73 points; 1-6 point scale) and a decrease in SNOT-20 scores at the end of treatment compared with placebo. 21 However, a study published by Videler et al, 22 23 the strength of recommendation for systemic antibiotic use in the treatment of CRSsNP is C (based on evidence from non-experimental descriptive studies, such as comparative studies, correlation studies, and case control studies). However, there is stronger evidence for the benefit of macrolide treatment in patients with CRS and normal IgE levels.…”
Section: Antimicrobialsmentioning
confidence: 99%